Do Spinoffs Create Value in Hong Kong? - Tai-Leung, Terence Chong; Wai-Hong, Daniel Wong; Liew, Venus Khim-Sen (Emerald Group Publishing Limited, 2006)
There is a broad consensus in the literature that spinoffs tend to create value for shareholders and exhibit positive long-run excess returns. However, most of the prior studies are confined to the US and the European cases. The spinoff problems in Hong Kong are surprisingly under-studied despite its important role as a global center of capital formation. In this paper, we find that there is a short-run value creation for the Hong Kong spinoffs. However, the financial health of the spinoff companies, measured by various financial ratios, tends to deteriorate in the long-run. In general, Hong Kong spinoffs generate negative returns to investors.